Amyloid-beta (Aβ1–42)-induced paralysis in Caenorhabditis elegans is reduced through NHR-49/PPARalpha. (21st June 2020) - Leiteritz, Anne; Baumanns, Stefan; Wenzel, Uwe
Highlights: NHR-49/PPAR-alpha inhibits the steroidal-signaling pathway in C. elegans. NHR49 increases nuclear translocation of stress-resistance enhancing transcription factor DAF-16. Fenofibrate activates NHR49 and reduces the Alzheimer phenotype in CL2006. Abstract: Alzheimer´s disease is a neurodegenerative disorder characterized by the misfolding and aggregation of amyloid β (Aβ). Agonists of peroxisomal proliferator-activated receptors (PPARs) are discussed as anti-amyloidogenic compounds, e.g. due to their cholesterol-lowering activities. In a previous study we have shown in Caenorhabditis elegans expressing human Aβ in muscle cells, that inhibition of steroid-signaling, by RNAi of respective members of the signaling pathway or by reducing cellular cholesterol uptake, both increases the nuclear translocation of the foxo transcription factor DAF-16 and concomitantly reduces Aβ-induced paralysis. Using RNAi in the present study we show that NHR-49/PPARalpha inhibits steroidal-signaling upstream of DAF-9, a cytochrome P450 -dependent enzyme which generates dafachronic acids as ligands for the nuclear hormone receptor DAF-12, and upstream of DAF-12 itself. The NHR-49/PPARalpha agonist fenofibrate reduces Aβ-induced paralysis in dependence on nhr-49 and nuclear translocation of DAF-16. In conclusion, activation of NHR-49/PPARalpha inhibits the steroidal-signaling pathway which increases the nuclear translocation of DAF-16 and inhibits the Aβ-induced phenotype in an Alzheimer model of C. elegans .